Analysis of the Quality of Learning Using Letter Board Media on Capabilities for Understanding and Recognizing Alphabets - Sihombing, Enjelina Vincere; Yana, Eka Yuli; Manalu, Ines (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Media is one of the keys to the running of the learning process. Concerning the importance of media for the quality of learning both in terms of understanding and recognition, the formulation of the problem in this research is whether students really understand correctly what has been learned in class through the use of learning media? . Based on the description of the problem, the aim of writing this research is to solve the problem of children's lack of knowledge regarding understanding and recognizing letters which is the basis of reading ability. The method used in this research is the Qualitative Method, namely a method that focuses on in-depth observation. Based on the research we have conducted, the use of letter board media not only provides children with an introduction and understanding of the alphabet. However, it also develops children's language skills in arranging letters to form new words thereby increasing children's vocabulary. The use of letter board media in learning is one of the recommendations from the author in improving children's understanding of the alphabet and new vocabulary in language development.